Formulation of Qur’anic Islamic Parenting Values: Pesantren Education Strategies in the Society 5.0 Era (A Comparative Study of Al-Tabari and Al-Azhar Tafsir) - M. Syauqii Shalkhi Al Farizi; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2026)
The rapid pace of social change and technological advancement in the Society 5.0 era requires educational institutions, including Islamic boarding schools (pesantren), to adapt by developing more human-centered and spiritually grounded learning systems. This study aims to formulate Islamic parenting values derived from the Qur’an through a thematic interpretation approach (tafsir maudhū’i), by examining Tafsir Al-Thabari and Tafsir Al-Azhar. Using a qualitative library research method combined with content analysis, this study explores key principles of Islamic parenting such as monotheism (tauhid), parental responsibility, empathy, gradual education, and the balance between rights and duties in child upbringing. The findings indicate that these values are deeply rooted in divine revelation, with Al-Thabari presenting a normative and textual interpretation, while Buya Hamka, through Tafsir Al-Azhar, offers a more reflective and contextual perspective relevant to contemporary life. These values are considered highly applicable to the pesantren education system, especially in responding to the challenges of digitalization and social transformation in the Society 5.0 era. By integrating these Islamic values into curricula and learning methods, pesantren can strengthen their role in nurturing a generation of students who are faithful, morally upright, and adaptive to modern developments. This research contributes to the development of an Islamic education model that remains contextually relevant while firmly rooted in Qur’anic teachings.